2016
DOI: 10.1162/evco_a_00146
|View full text |Cite
|
Sign up to set email alerts
|

Binary Image Classification: A Genetic Programming Approach to the Problem of Limited Training Instances

Abstract: In the computer vision and pattern recognition fields, image classification represents an important yet difficult task. It is a challenge to build effective computer models to replicate the remarkable ability of the human visual system, which relies on only one or a few instances to learn a completely new class or an object of a class. Recently we proposed two genetic programming (GP) methods, one-shot GP and compound-GP, that aim to evolve a program for the task of binary classification in images. The two met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The method in [19], on the other hand, has successfully been designed to evolve rotation-invariant image descriptors and extensively examined; however, the length of the feature vector is static and a parameter tuning phase is needed to determine this parameter. The methods in [44], [45], and [46] were not able to cope with rotation as we have observed in our experiments. Hence, this paper substantially extends those methods to evolve rotation-invariant image descriptors, dynamically determining the length of the feature vector, extensively evaluating the evolved descriptors, and providing a deep analysis.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…The method in [19], on the other hand, has successfully been designed to evolve rotation-invariant image descriptors and extensively examined; however, the length of the feature vector is static and a parameter tuning phase is needed to determine this parameter. The methods in [44], [45], and [46] were not able to cope with rotation as we have observed in our experiments. Hence, this paper substantially extends those methods to evolve rotation-invariant image descriptors, dynamically determining the length of the feature vector, extensively evaluating the evolved descriptors, and providing a deep analysis.…”
mentioning
confidence: 61%
“…In other words, additional data may degrade the performance as it increases the possibility of noisy instances. In some of our recent work [19], [44]- [46], we also observed that GP can evolve a good keypoints detection or feature extraction model using only a limited number of training instances. Both [19] 1 and [46] are directly related to the work of this study.…”
mentioning
confidence: 86%
“…GP has been widely used for image analysis [35], [36], [37], [38], where typical works are reviewed in this section. A detailed description of this work is beyond the scope of this article, readers are refereed to [39], [40], [41], [42], [43], [44], [45] for more work on EC or GP for image analysis.…”
Section: Image Analysis Using Genetic Programmingmentioning
confidence: 99%
“…In [4], two GP-based methods are studied for binary image classification tasks. These methods aim at evolving a classifier using a few instances per class.…”
Section: Related Workmentioning
confidence: 99%
“…Feature construction is the process of creating new, high-level features, often by combining multiple existing features [14,4]. Constructed features generally better describe an instance than a single existing feature, reducing the number of features required, which reduces the size of the search space a classifier must train on.…”
Section: Introductionmentioning
confidence: 99%